ANALYSIS OF INNOVATION, MOTIVATION, AND CAPABILITY ON INTEGRATED ECOTOURISM PERFORMANCE IN WAGOM VILLAGE, PARIWARI DISTRICT, FAKFAK DISTRICT - Abdurrasyid Wadjo; Sundjoto Sundjoto; Titis Istiqomah; Untung Tamsil (Jurnal Scientia, 2023)
The exotic existence in Wagom sub-district has great potential to be developed as an integrated ecotourism area. The research aims to determine the dynamics of innovation, motivation and capability of local communities towards efforts to develop integrated ecotourism as a superior economic source for Fakfak Regency. Descriptive research with a qualitative approach was carried out from August to December 2023. The analytical tool used was a modified Ishikawa diagram combined with weighting techniques. Data was obtained from in-depth interviews, using closed and repeated questionnaires, and validated using cross-triangulation techniques. The population includes the people of Fakfak district and several immigrants who were determined randomly and deliberately. The total research sample was 134 people. The results of the analysis show that innovation and community motivation are very positive; but not yet supported by capabilities that are still low. Thus, to develop superior integrated ecotourism, it is necessary to form a special working group consisting of members of the Wagom community themselves who are trained to have strong competence, integrity and credibility as a manifestation of the management capability of tourism implementers to be competitive.